(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to examine the role of purchase intention as a mediator variable in the relationship between digital marketing, product quality, and service quality on purchasing decisions, with a case study on customers of Toko Buket Dama Florist. In today’s digital era, marketing strategies through digital media are becoming increasingly important, especially in creative industries such as flower bouquet sales. In addition, product and service quality are also determining factors in building consumer trust and interest. This study uses a quantitative approach with a survey method on customers who have made purchases at Dama Florist. This study uses a nonprobability sampling method of purposive sampling type where samples are taken based on certain criteria that must be met. Sampling in this study uses the Slovin formula. Data analysis was carried out using Smart PLS 4.0. The results of the data analysis show that digital marketing and product quality have an effect on purchase interest, service quality does not affect purchasing decisions with purchase interest, product quality does not affect purchasing decisions, service quality affects purchasing decisions, digital marketing affects purchasing decisions with purchase interest as an intervening variable, product quality affects purchasing decisions with purchase interest as an intervening variable, and service quality does not affect purchasing decisions with purchase interest as an intervening variable.